Computer Vision Syndrome Prevalence and Associated Factors Among the Medical Student in Kist Medical College - Basnet, Anjila; Basnet, Pragya; Karki, Poojyashree; Shrestha, Shriraj (Nepalese Medical Journal, 2018)
Correction: In the publication, the study period was missed. The study period "from 2nd April 2018 to 15th April 2018" has been added. Introduction: Computers and other visual display terminals are now an essential part of our daily life. In the present era, use of computer has increased many folds, and its use has been associated with increased health risks, especially eyes. Materials and Methods: This hospital-based prospective, observational, descriptive study. “Specific Computer Users Questionnaire’’regarding the visual symptoms was put used. Schirmer’s test –I, and Tear film break up time were evaluated in all students. Results: Among 100 medical students 74% of the medical students sampled who used to spend 2 hours or more on their digital screens on a daily basis were complaining of one or more of CVS manifestation. Eye strain, burning eyes, neck, shoulder, or back pain, dryness, irritation and redness of eyes, headaches during or after working on computer and overall body fatigue were recorded in 89%,87%,78%,77%,71%and 68% respectively. Dry eye was associated with CVS in 58 % in right eye and 55% in left eye according to-Tear film break up time measurement whereas 59% students have dry eye in right eye and 57% students have dry eye in left eye according to Schirmer’s test – I measurement. Conclusions: Symptoms of CVS increase with increased duration of working on digital screens for 2 hours or more. The factors associated with the severity of CVS were hours of digital screens use per day and dry eye.